2013
DOI: 10.1111/ajt.12408
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Performance in Pediatric Liver Transplant Recipients

Abstract: To date, the course of cognitive development in children after liver transplantation (Ltx) is poorly understood. Cognitive performance, however, is crucial in all developmental stages and for educational achievement. This cross‐sectional single‐center study examined the prevalence of long‐term cognitive impairment in a cohort of 64 pediatric patients after Ltx. Median age at Ltx was 12 months. The revised Wechsler Intelligence Scale IV was administered to assess cognitive performance. Patients were compared wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
51
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(57 citation statements)
references
References 44 publications
4
51
1
1
Order By: Relevance
“…Although no higher education was reported in our pediatric cohort, statistic confounders and the patient's young age or socioeconomic background must be considered. Children surviving liver transplantation are at risk of prolonged cognitive and academic deficits …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although no higher education was reported in our pediatric cohort, statistic confounders and the patient's young age or socioeconomic background must be considered. Children surviving liver transplantation are at risk of prolonged cognitive and academic deficits …”
Section: Discussionmentioning
confidence: 99%
“…Children surviving liver transplantation are at risk of prolonged cognitive and academic deficits. (25,26) Patients with an initial diagnosis of ABCB4 disease in adulthood may display a clinical phenotype with a later onset, such as ICP; alternatively, clinical or laboratory signs of the disease could have been misinterpreted or overlooked. These patients typically present with a heterogeneous clinical picture.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Kaller et al . suggested that there might be a critical period for liver disease to affect the brain during early childhood, and that if LT is performed very early in life, neuronal plasticity might alleviate the potential toxic influences . They also showed that children who received LT within the first year of life had a normal cognitive outcome compared with the mean .…”
Section: Discussionmentioning
confidence: 99%
“…The same study also determined that the neurologic status of children who underwent a liver transplant because of a genetic metabolic disorder was even worse. 31 Therefore, some liver transplant patients should continue their education in special education centers. Health professionals should evaluate recipients who repeat a grade, have excessive absences or drop out of school in terms of their special education needs and should refer them to special education centers.…”
Section: Discussionmentioning
confidence: 99%